Human Chorionic Gonadotropin and CA 15-3 Producing Adenocarcinoma - Üçkaya, G.; Özet, A.; Arpaci, A.; Kömiircü, S. (Nuklearmedizin - NuclearMedicine, 1998)
50 years old man suffering from primary lung adenocarcinoma presented with high levels of both beta subunit human chorionic gonadotropin (βHCG) and cancer antigen 15-3 (CA 15-3) in the absence of elevated carcinoembrionic antigen (CEA), alfa fetoprotein (AFP) and carbohydrate antigen 19-9 (CA 19-9). Although βHCG or CA 15-3 high levels were reported in adenocarcinoma of lung, this is the first report of a patient with high levels of both markers.
Keywords: Lung cancer; tumor markers; βHCG; CA 15-3